PERANAN PIMPINAN DALAM MENINGKATKAN PELAYANAN PADA CV. ANUGERAH NIAGA DI KOTA PADANG - Meilina, Susiyanti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Customer satisfaction or dissatisfaction is determined, among others, by a service that is desired by customers. Quality assurance is a top priority for Honda motorcycle dealers, who at this time in particular are used as a benchmark for the competitive advantage of Honda motorcycle dealers. In providing satisfaction services to customers CV. Anugerah Niaga gives more priority to other Honda motorcycle dealers. The purpose of this study is to find out: 1) the role of the leader in improving customer service such as Honda motorcycles; 2) constraints faced by the leadership in improving motorcycle customer service; 3) efforts made by the leadership in improving customer service for Honda motorcycles on the CV. Anugerah Niaga in the City of Padang. This type of research is qualitative research using descriptive methods, namely the problem solving procedure investigated by describing or describing the condition of the subject or object of research of a customer or recipient of service and society at present based on facts that are visible and as they are. The selection of informants in this study was selected by incidental sampling which is sampling by taking individuals who can be reached or encountered .. The data types are primary data and secondary data collected through interviews, observation, and library research. The analysis technique used is qualitative analysis. The results of this study indicate that: activities carried out by the leadership of CV. Angerah Niaga not only makes sales, but also serves motorcycle service. To service service services, there is a need for service quality standards provided by the company so as to provide even satisfaction for all consumers. In an effort to improve service quality standards, the leadership conducted a series of training and development. The conclusion that can be taken is the service in the sale of Honda motorbikes by the leadership of CV, Anugerah Niaga able to protect consumers by convincing consumers even though there are still obstacles faced and efforts to overcome these obstacles. Suggestions are to make selling procedures more convenient; sales conditions are somewhat relaxed; the best service procedures for consumers; and maintain achievement by increasing employee and consumer loyalty.